THE ROLE OF FISHERMAN WIFE IN IMPROVING HOUSEHOLD INCOME IN PONDOK BATU VILLAGE SARUDIK SUB DISTRICT TAPANULI TENGAH REGENCY SUMATERA UTARA PROVINCE - Efrita Nainggolan; Ridar Hendri; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in April 2016 located in Pondok BatuVillage, Sarudik Subdistrict, Tapanuli Tengah Regency, North SumateraProvince. The purpose of this study is to describe the characteristics offishermen's wive, to analyze the time division of the fisherman wife between therole of housewife and the additional income earner and to describe the role of thefisherman wife in increasing the household income. The method used in thisresearch is survey method. Respondents in this research is the wife of fishermanwho work outside the house amounted to 25 peopleBased on the research result that the role of fisherman wife in increasingthe household income of fisherman have characteristic that generally aged (16-45years old) is classified as very productive age with number 22 soul. Educationlevel of fisherman wife is elementary school graduate amounted to 14 soul, themost dominant family count is 6-7 with 13 souls. Experience of wife of fishermanwork that is> 8 year with amount of 17 soul. Curious working hours given by thefisherman's wife are as daily necessity traders around 84 hours / week, asprocessing of fishery products about 28 hours / week, as factory workers about 56hours / week and as animal raising around 28 hours / week. The average incomeearned by fishermen's wife every month from the profession as the processing offishery products as much as Rp.625.900, as a day-to-day trader of Rp. 350.000, asfactory worker of Rp. 500.000 and animal raising Rp.430.000Key words: Role, Fisherman’s wife, Pondok Batu